Ethical responsibilities of tenured academics supervising non-tenured researchers in times of neoliberalism and precarity. (2nd January 2022) - Smithers, Kathleen; Harris, Jess; Goff, Mhorag; Spina, Nerida; Bailey, Simon
ABSTRACT: Neoliberal reform of the university sector has resulted in increasing numbers of academics employed on casual or fixed-term contracts. While there is an emergent body of literature on issues of precarity in the academy, relatively little attention has been paid to the roles and responsibilities of those tenured academics who employ and manage non-tenured researchers. The work involved in hiring and managing a contract researcher is rarely acknowledged or supported, and managers receive little to no training. In this paper, we draw on Dorothy Smith's feminist sociological approach to analyse interviews with 22 non-tenured researchers to examine how managerial relationships shape the employment experiences of those working precariously. We argue that tenured academics have ethical responsibilities to provide a working environment that is fair, supports the ongoing development and wellbeing of non-tenured staff, and challenges dominant discourses of precarious academics as 'other'.